2004
DOI: 10.1016/j.femsle.2004.06.021
|View full text |Cite
|
Sign up to set email alerts
|

In vivo induced antigenic determinants of Actinobacillus actinomycetemcomitans

Abstract: Actinobacillus actinomycetemcomitans is a Gram-negative capnophilic rod and the etiological agent of localized aggressive periodontitis. The genome-wide survey of A. actinomycetemcomitans using in vivo induced antigen technology (IVIAT) has previously resulted in the discovery of antigenic determinants expressed specifically in diseased patients. The present study evaluated the potential of these antigens as putative disease markers, and investigating their contribution to the pathogenesis of the microorganism… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(35 citation statements)
references
References 24 publications
3
32
0
Order By: Relevance
“…Also, consistent with the anaerobic gut environment, IVIAT identified glycolytic enzymes, hydrogenases involved in fermentation of carbon compounds, an alcohol dehydrogenase, and reductases (including two cryptic nitrate reductases) involved in energy generation from carbohydrates via anaerobic respiration and fermentation (42). These results were expected and consistent with those of other studies of diverse organisms using techniques such as transcriptional profiling (59), in vivo expression technology (15,33), recombinase in vivo expression technology (4), signature-tagged mutagenesis (14,37,38), selective capture of transcribed sequences (SCOTS) (7), and IVIAT of other organisms (5).…”
Section: Resultssupporting
confidence: 88%
“…Also, consistent with the anaerobic gut environment, IVIAT identified glycolytic enzymes, hydrogenases involved in fermentation of carbon compounds, an alcohol dehydrogenase, and reductases (including two cryptic nitrate reductases) involved in energy generation from carbohydrates via anaerobic respiration and fermentation (42). These results were expected and consistent with those of other studies of diverse organisms using techniques such as transcriptional profiling (59), in vivo expression technology (15,33), recombinase in vivo expression technology (4), signature-tagged mutagenesis (14,37,38), selective capture of transcribed sequences (SCOTS) (7), and IVIAT of other organisms (5).…”
Section: Resultssupporting
confidence: 88%
“…This was accomplished by using IVIAT, which identifies genes that are expressed by a pathogen during an actual infection process. IVIAT has been previously applied to other gram-negative organisms, mycobacteria, and yeast (3,4,8,18,24), but this is the first report of the use of this technology in a gram-positive organism. The basis of IVIAT is that pooled sera from patients with disease adsorbed against in vitro-derived GAS antigens can be used to identify genes upregulated in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…The technique has been used to screen the entire A. actinomycetemcomitans genome and revealed 116 in vivo expressed antigens [23]. Further investigations using this method have shown that patients have a significantly greater serum antibody titer against six antigens than healthy controls, which supports the in vivo expression of these antigens, and even suggests their usefulness as disease markers [24].…”
Section: Introductionmentioning
confidence: 92%